The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1093/intqhc/mzab092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating factors associated with the cancellation and delay of elective surgical procedures: a systematic review

Abstract: Background Elective surgery cancellation is considered a fundamental problem in health care services—it causes considerable disruption to patient flow, further eroding often already stretched operating capacity, and consequentially reduces both hospital performance and patient satisfaction. This research presents a systematic review (SR) of the reasons for surgery cancellation among different hospitals and countries. By highlighting these causes, we identify how to reduce cancellations thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…A systematic review has reported that the main causes of surgery cancellations were hospital-related causes, such as improper scheduling, and patient-related causes, such as patient refusal. 7 In Japan, 19 cases of medical accidents involving the continued administration of medications that were supposed to be withdrawn before a hematological procedure were reported between 2010 and 2015, including three that could have resulted in patient disability. 8 Perioperative bleeding is recognized as a major risk factor for subsequent mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has reported that the main causes of surgery cancellations were hospital-related causes, such as improper scheduling, and patient-related causes, such as patient refusal. 7 In Japan, 19 cases of medical accidents involving the continued administration of medications that were supposed to be withdrawn before a hematological procedure were reported between 2010 and 2015, including three that could have resulted in patient disability. 8 Perioperative bleeding is recognized as a major risk factor for subsequent mortality.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been observed in previous research examining patient no-shows for elective surgery, which also acknowledge the difficulty in resolving this issue. [12][13][14] As BS is a limited resources for patients living with severe obesity in Canada, 32 United States, 33 and outside of North America 34 with fewer than 1% of all eligible patients receiving this intervention, 35 The use of peer mentors could be a cost-effective option to supplement professional support, and has been suggested by both patients and HCPs to help alleviate patient anxiety. The need for peer mentors has been previously reported among patients waiting for BS.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 These fears were often made worse after reading about experiences on Internet support groups. 12,13 Finally, patients and HCPs identified logistical issues such as costs related to mandatory pre-operative meal-replacement or postoperative vitamin supplementation, 14,15 a lack of personal supports for post-operative care, 16,17 a major life event, 18,19 and proximity to the BCoE 20 as major factors contributing to the decision to selfwithdraw from scheduled BS.…”
Section: Factors Contributing To the Decision To Selfwithdraw From Sc...mentioning
confidence: 99%
See 2 more Smart Citations